EVALUASI TENTANG PENGETAHUAN KEWIRAUSAHAAN DALAM MENINGKATKAN INTENSI BERWIRAUSAHA (STUDI PADA MAHASISWA POLITEKNIK NEGERI BENGKALIS) - Try Handayani (Inovbiz: Jurnal Inovasi Bisnis, 2016)
Abstract:  This   study  aims  to  determine  the   level  of   Entrepreneurship knowledge and its influence on student entrepreneurship intentions State Polytechnic of Bengkalis. This study uses a quantitative approach with survey method   which   focuses   on   explanation   of   causal   relationships   between variables. Sampling using Taro Yamane or Slovin formula thus obtained a sample of 82 respondents. The number of samples have been obtained is then determined the amount of each sample according to the number of students in each course of study is proportionate random sampling. Sampling using probability sampling technique with random sampling method. Data collected through questionnaires to the respondents. Data was analyzed by descriptive technique. The results showed that the level of Entrepreneurship knowledge Bengkalis Polytechnic students are at high scale which includes knowledge about the efforts that will be entered or initiated, roles and responsibilities in entrepreneurship, and knowledge of management and business organizations in entrepreneurship. Furthermore, the results showed that the Entrepreneurial intentions Bengkalis Polytechnic students are at high scale. This suggests that increasing  entrepreneurial  knowledge  becomes   one  of   the  factors  that influence the Entrepreneurial intentions in Bengkalis Polytechnic student. Keywords: Pengetahuan Kewirausahaan, Intensi Kewirausahaan.